2005
DOI: 10.1074/jbc.m502255200
|View full text |Cite
|
Sign up to set email alerts
|

Proteins in Human Brain Cortex Are Modified by Oxidation, Glycoxidation, and Lipoxidation

Abstract: Diverse oxidative pathways, such as direct oxidation of amino acids, glycoxidation, and lipoxidation could contribute to Alzheimer disease pathogenesis. A global survey for the amount of structurally characterized probes for these reactions is lacking and could overcome the lack of specificity derived from measurement of 2,4-dinitrophenylhydrazine reactive carbonyls. Consequently we analyzed (i) the presence and concentrations of glutamic and aminoadipic semialdehydes, N ⑀ -(carboxymethyl)-lysine, N ⑀ -(carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
245
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(254 citation statements)
references
References 48 publications
8
245
1
Order By: Relevance
“…We also showed that the levels of MDA-modified vimentin increased as SAMP8 mice age, and this increase was coupled to a decrease in IgMs against vimentin and MDA. Athough MDA-modified vimentin was previously identified in the brain cortex of Alzheimer's patients via a proteomic screen of MDA-oxidized proteins (45), astrocytes in the brain demonstrate age-related changes that resemble those of the SASP, including expression of several cytokines, accumulation of proteotoxic aggregates, and elevated levels of vimentin (96). Nonetheless, the accumulation of MDA-modified vimentin detected in SAMP8 mice may also reflect senescence-independent cellular changes in response to DNA-damage signaling constitutively occurring in this mouse strain (97).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also showed that the levels of MDA-modified vimentin increased as SAMP8 mice age, and this increase was coupled to a decrease in IgMs against vimentin and MDA. Athough MDA-modified vimentin was previously identified in the brain cortex of Alzheimer's patients via a proteomic screen of MDA-oxidized proteins (45), astrocytes in the brain demonstrate age-related changes that resemble those of the SASP, including expression of several cytokines, accumulation of proteotoxic aggregates, and elevated levels of vimentin (96). Nonetheless, the accumulation of MDA-modified vimentin detected in SAMP8 mice may also reflect senescence-independent cellular changes in response to DNA-damage signaling constitutively occurring in this mouse strain (97).…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin was previously found to be modified by MDA in the human brain cortex of Alzheimer's patients and by CML in skin fibroblasts isolated from elderly donors and exposed to UV light (44,45). Given that vimentin is the target of various posttranslational modifications that include oxidation (46,47), we thus examined whether these oxidative adducts were associated with vimentin exposed on the surface of senescent cells.…”
Section: H4 Recognizes Vimentin and Oxidative Posttranslational Modimentioning
confidence: 99%
“…This increased β-amyloid protein -induced oxidative stress in conjunction with decreased neurotrophic support [17] are the major determinants of AD. Studies undertaken in post-mortem brain samples obtained from AD patients have shown extensive lipid, protein and DNA oxidation [7]. Neural tissues of AD patients exhibit increased levels of peroxidation end-products such as malondialdehyde (MDA), 4-hydroxynonenal, carbonyls and other species [18].…”
Section: Molecular Pathophysiology Of Alzheimer's Diseasementioning
confidence: 99%
“…Increased protein, lipid and DNA oxidation has been demonstrated in brain samples of AD patients [6]. Protein carbonyl 3, 3'-dityrosine and 3-nitrotyrosine levels in post-mortem brain samples of AD patients exhibit increased oxidative and nitrosative protein modification in the hippocampal and neocortical regions [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are hundreds of oxidized proteins in the brain; exist qualitative and quantitative differences between control and diseased brain [74,75], and proteomics represents a powerful approach to study protein oxidation [76]. In the AD brain, oxidation is observed in regions where amyloid b-peptide (Ab) 1-42 is present, but not in cerebellum where AD pathology is not observed [77,78].…”
Section: Antioxidant Proteinsmentioning
confidence: 99%